A Cancer Cell Membrane‐Derived Biomimetic Nanocarrier for Synergistic Photothermal/Gene Therapy by Efficient Delivery of CRISPR/Cas9 and Gold Nanorods. Issue 16 (19th June 2022) - Huang, Lin; Zhou, Mengyang; Abbas, Ghulam; Li, Chao; Cui, Mengmeng; Zhang, Xian‐En; Wang, Dian‐Bing
Abstract: Bimodal synergistic therapy produces superadditive effect for enhanced therapeutic efficacy. However, how to efficiently and simultaneously deliver several kinds of therapeutic agents is still challenging. A cancer cell membrane‐derived nanocarrier (mCas9‐sGNRs) is proposed for synergistic photothermal/gene therapy (PTT/GT) by efficient delivery of clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated protein 9 (Cas9) and gold nanorods (GNRs). In this approach, Cas9 proteins can be efficiently loaded inside the cell membranes (mCas9) by electrostatic interactions. Similarly, single‐guide RNAs, which target survivin, can be loaded onto GNRs (sGNRs) through electrostatic interactions and encapsulated by mCas9. As a result, the nanodelivery systems present advantages in biocompatibility, homologous targeting capacity and loading efficiency of cargoes. In addition, significant antitumor effects is achieved by gene editing of survivin which induces anticancer activity and reduces heat tolerance of cancer cells caused by GNRs mediated PTT due to the downregulation of HSP70. These results indicate the nanotherapeutic platform leads to enhanced PTT/GT efficacy. Therefore, this work not only provides a general strategy to construct a versatile nanoplatform for loading and target delivery of several therapeutic cargos but will also be valuable for PTT/GT and other bimodal synergistic therapy. Abstract : A new cancer cell membrane‐derived nanocarrier (mCas9‐sGNRs) is constructed for synergistic photothermal/gene therapy (PTT/GT) by efficient delivery of clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR‐associated protein 9 (Cas9) and gold nanorods (GNRs). The designed nanocarrier achieves excellent targeting capacity, high loading efficiency and significant antitumor effects.